Sustainability of energy development in China - Zoryna, Tatsiana G.; Xueyao, Liu; Zhuxi, Yang (Journal of the Belarusian State University. Economics, 2022)
This paper discusses the indicators and method to evaluate the sustainability of energy development and analyse the current situation of sustainability of energy development in China. There are comparison and analysis on sustainability of energy development between China and other countries and among provinces of China. In China, the sustainability of energy development is relatively poor and there are no significant differences among provinces. Due to unbalanced resource distribution, the sustainability of energy development varies with different factors. Based on the characteristics and degrees of sustainability of energy development in various countries and provinces of China, the possible advices are proposed to optimise the energy development.